การสึกของกลาสไอโอโนเมอร์ซีเมนต์ภายหลังการแปรง - พีรพงศ์ กุประดิษฐ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Objective: To compare the physical property in abrasive wear of 2 conventional glass ionomer cements (Ketac Fil Plus Aplicap®, Fuji IX GP capsule®) and 2 resin modified glass ionomer cements (Ketac N-100®, Fuji II LC capsule®) after brushing, in vitro. Materials and methods: 128 Specimens were prepared in metal molds. The samples were divided into 4 equally groups according to materials tested. Volume and mean depth of surface of each sample was determined using profilometer (TalyScan 150, Taylor Hobson LTD., England). The specimens were brushed by automatic brushing machine (V-8 CrossBrushing Machine, SABRI Dental Enterprises, Inc., U.S.A.). 8 Samples were used per cycle, at 20,000 strokes, 90 cycles per minute, with a brush-head load of 150 grams in the toothpaste slurry (Colgate®). Changes in volume and mean depth of each sample after brushing were measured and calculated. The data were analyzed using Kruskal-Wallis test at a significant level 0.05. Results: Changes in volume and mean depth after brushing of Ketac Fil Plus Aplicap® were more than those of Fuji IX GP capsule®, Fuji II LC capsule® and Ketac N-100®. Ketac Fil Plus Aplicap® generally showed significant different in wear more than Ketac N-100®, Fuji II LC capsule® and Fuji IX GP capsule® (P = 0.0025, 0.0047, 0.031 respectively), but there was no significant difference in wear among Fuji IX GP capsule® and Fuji II LC capsule® or Ketac N-100®. Conclusion: Ketac Fil Plus Aplicap® generally were more than the resin modified glass ionomer cements (Ketac N-100®), Fuji II LC capsule®) and the another conventional glass ionomer cements (Fuji IX GP capsule®).